Ceramic shell waste valorization: A new approach to increase the sustainability of the precision casting industry from a circular economy perspective. (15th February 2023) - Oliveira, K.A.; Simão, L.; Rebouças, L.B.; Hotza, D.; Montedo, O.R.K.; Novaes de Oliveira, A.P.; Raupp-Pereira, F.
Graphical abstract: Highlights: Metrics for the advancement of the circular economy were proposed; Classification, Potentiality, Quantity/viability, and Applicability were evaluated; Ceramic Shell Waste was used as a case study; Ceramic filters and refractory aggregates were suggested as products. Abstract: The problem of waste generation has grown because of the need to extract natural resources, obtain materials, and consume energy to meet current societal needs. Many studies have been conducted worldwide in favor of technological solutions for the valorization of industrial waste (IW) but few discussed relevant data for effective recovery. In this study, a case study of ceramic shell waste (CSW) was performed using, for the first time, a waste valorization system based on the classification, potentiality, quantity/viability, and applicability criteria (CPQvA) in a specific region (Brazil). CPQvA is a multicriteria decision-making system that acts as a guide to help managers and researchers connect the potential of IW with the feasibility of its application in a product or another process. Using the proposed systematic criteria, it was possible to demonstrate similarities and differences in waste applications. Thirteen possible products made from CSW were analyzed based on all the parameters of CPQvA. Ceramic filters and refractory aggregates were the most viable products. Creating public policies that encourage the use of waste as a raw material could make the precision casting industry process cleaner and the economy more circular.